Artemisinin Mediates Its Tumor-Suppressive Activity in Hepatocellular Carcinoma Through Targeted Inhibition of FoxM1 - Nandi, Deeptashree; Cheema, Pradeep Singh; Singal, Aakriti; Bharti, Hina; Nag, Alo (Frontiers in Oncology, 2021)
The aberrant up-regulation of the oncogenic transcription factor Forkhead box M1 (FoxM1) is associated with tumor development, progression and metastasis in a myriad of carcinomas, thus establishing it as an attractive target for anticancer drug development. FoxM1 overexpression in hepatocellular carcinoma is reflective of tumor aggressiveness and recurrence, poor prognosis and low survival in patients. In our study, we have identified the antimalarial natural product, Artemisinin, to efficiently curb FoxM1 expression and activity in hepatic cancer cells, thereby exhibiting potential anticancer efficacy. Here, we demonstrated that Artemisinin considerably mitigates FoxM1 transcriptional activity by disrupting its interaction with the promoter region of its downstream targets, thereby suppressing the expression of numerous oncogenic drivers. Augmented level of FoxM1 is implicated in drug resistance of cancer cells, including hepatic tumor cells. Notably, FoxM1 overexpression rendered HCC cells poorly responsive to Artemisinin-mediated cytotoxicity while FoxM1 depletion in resistant liver cancer cells sensitized them to Artemisinin treatment, manifested in lower proliferative and growth index, drop in invasive potential and repressed expression of EMT markers with a concomitantly increased apoptosis. Moreover, Artemisinin, when used in combination with Thiostrepton, an established FoxM1 inhibitor, markedly reduced anchorage-independent growth and displayed more pronounced death in liver cancer cells. We found this effect to be evident even in the resistant HCC cells, thereby putting forth a novel combination therapy for resistant cancer patients. Altogether, our findings provide insight into the pivotal involvement of FoxM1 in the tumor suppressive activities of Artemisinin and sheds light on the potential application of Artemisinin for improved therapeutic response, especially in resistant hepatic malignancies. Considering that Artemisinin compounds are in current clinical use with favorable safety profiles, the results from our study will potentiate its utility in juxtaposition with established FoxM1 inhibitors, promoting maximal therapeutic efficacy with minimal adverse effects in liver cancer patients.